"Risky" Subjects: Theorizing Migration as Risk and Implications for Newcomers in Schools and Societies. Issue 1 (2nd January 2018) - Rodriguez, Sophia
Abstract : This article theorizes migration as risk, drawing on Biesta's notion of risk. The author explores how productive risk connects with emancipation, seeing the risky migrant subjects in societies in new ways, rather than positioning them as marginalized threats. Finally, the author connects the theory of migration as risk to current qualitative data from empirical research on newcomer migrant youth in the United States. Implications of the theorizing are also discussed.